Animal Soundscapes and Early Modern Privacy at the Danish Court - Jeanneret, Christine (Privacy Studies Journal, 2026)
European courts were noisy and crowded spaces during the seventeenth century, not least because of the many animals they harboured. Dead or alive animals at court served various purposes: tokens of power such as horses and dogs with a military or entertaining function; “objects” of prestige with decorative functions such as exotic living animals or dead animal parts in the prestigious ivory and narwhal collection preserved at Rosenborg Castle; companions in an intimate and private relationship with their owners; and workforce in agriculture or as modes of transport. Historians rarely listen, and if they do, they listen mostly to humans, in a traditional speciesist approach. However, one of the most characteristic features of animals is their sonic world: horse hooves, birdsongs, or barking dogs are some of the omnipresent animal soundscapes at court, creating a common soundscape and a shared aurality. In this article, I study the sounds and vocalizations produced by various animals that were kept at the Danish court, based on textual and visual sources, along with the artefacts preserved in the royal collection of Rosenborg Castle. The purpose is to reconstruct the sonic ecology of the animals at court in order to understand the interspecies relations and the respective influence of humans and nonhumans in terms of privacy. What do the sources tell us about animal and human interaction in terms of privacy, if we ask the right questions to these sources? Issues of privacy, invasion of privacy, intimacy, and violence are considered, based on the aural world of animals.